Peningkatan Higiene Sanitasi Dapur Sentral PT XYZ dengan Analisis VRIO (Valuable, Rare, Imitate to Cost, Organized) - Tobing, Febby Barita Lumban; Sugiyono, Sugiyono; Rahayu, Winiati P. (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2025)
Cases of food poisoning often originate from households or food service businesses that do not follow proper handling procedures. PT XYZ is a food service business with a central kitchen that supplies 60 outlets. This study aimed to analyze the implementation of hygiene and sanitation practices during operations using the VRIO method, conducted in three research stages. The company demonstrated a commitment to hygiene and sanitation, with observations showing a compliance rate of 80.04%, categorized as good. However, the company had not yet obtained formal certification. A strong correlation (p